The concept of the Sun as á¼¡Î³ÎµÎ¼Î¿Î½Î¹ÎºÏŒÎ½ in the Stoa and in Manilius’ Astronomica (Revista Archai, 2017)
Hegemonikon in Stoic vocabulary is the technical term for the chief part or ‘command-centre’ of the soul. As we know, the Stoics considered the cosmos a living organism, and they theorised both about the human soul’s Hegemonikon and about its counterpart in the World-soul. My ultimate purpose in this paper is to show that the Stoic concept of the cosmic hegemonikon can be observed in Manilius’ Astronomica. The paper is divided in two parts. To begin with, I will examine and discuss the evidence concerning this concept in the relevant texts of the Early and Middle Stoa. The analysis will make clear that by the time of Manilius the concept of hegemonikon involved a background of astronomical theory introduced by the Stoic Posidonius. In the second section, I will go on to relate the concept of hegemonikon to the doctrines conveyed by Manilius. Additionally, we shall see that Manilius’ polemic allusions to Lucretius’ De Rerum Naturasuggest that the concept was intensely debated in the Post-Hellenistic philosophical circles.